Programming and Researching _With_ Youth in Cultural Institutions – a Brief Reflection on a Cross-Institutional Youth Advisory Board - Carolina Silva (Journal of Participatory Research Methods)
This brief report describes the operational processes and participatory methods involved in setting up, managing and mediating a cross-institutional youth advisory board. Youth advisory boards in museums give young people opportunities to co-program with and for their peers, as well as to have an active and visible role inside institutions. Framed by the research project _Youth in Museums_, the youth advisory board _Listening Lab – Youth, Culture, Participation_, was co-organized and developed with five cultural institutions in Lisbon, Portugal. These included the Museum of Art, Architecture and Technology (MAAT), BoCA – Biennal of Contemporary Art, Casa da Cerca – Contemporary Art Centre, LU.CA – Luís de Camões Theatre and the Municipal Galleries. Young people, aged 15 to 25, were invited to participate in group roundtables to discuss specific issues related to youth arts programs. In the sessions with the youth advisory board I combined a semi-structured approach with participatory methods that activated collective processes of meaning making.